Analysis of gain saturation in In0.02Ga0.98N/In0.16Ga0.84N multiple quantum wells - Kyhm, K; Taylor, R; Ryan, J; Someya, T; Arakawa, Y (2001)
A way of analyzing the data in a variable stripe length method gain experiment is presented. We confirm that the stripe length dependence of the gain in In0.02Ga0.98N/In0.16Ga0.84N multiple quantum wells is caused by the change of the chemical potential along the excited stripe due to the interaction of the carrier and photon densities, and the gain threshold density is estimated. A trial function assuming a Lorentzian line shape for the stripe length dependence of the gain is compared with the edge emission intensity as a function of the stripe length. This is found to fit very well with our data, even beyond the saturation region. © 2001 American Institute of Physics.